Analisis Kemampuan Menulis Teks Prosedur Siswa Kelas XI SMA Negeri 8 Medan Tahun Pembelajaran 2023/2024 - Mayang Putri; Abdurahman Adisaputera (Lembaga Pengembangan Kinerja Dosen, 2024)
The location where the research was carried out was SMA Negeri 8 Medan, which is on Jl. Pandau Hulu II, Sampali No. 23 Medan City District, Medan Area, North Sumatra, 20233 This study was carried out in June 2024. Through descriptive research, this study examines students' writing abilities in procedure text material. 34 SMA Negeri 8 Medan class XI students participated in this research. According to the findings of this study, the procedure text's content received an average score of 26.32 out of 100, placing it in the Good category at 75.21 percent. The number then was 825 for the procedural text structure aspect, with an excellent percentage of 80.88 percent and an average score of 24.26. The number is 1001 for the semantic part of procedural texts with a typical score of 29.44 and an excellent level of 84.12%. 2. According to KKM 75, the ability to write procedural texts is demonstrated by the fact that 27 students (79.41 percent) have completed the Indonesian Language KKM and 7 students (20.59 percent) have not completed the Indonesian Language KKM. 3. In view of the examination of achievement rates, the capacity to compose methodology texts of 16 understudies (47.06%) was in the excellent class, trailed by 15 understudies (44.12%) in the great class, 3 individuals (8.82%) in the great class. moderate, 0 understudies (0%), and 0 understudies (0%) in the unfortunate class.